Field resistance status of hot pepper to the pepper yellow leaf curl Indonesian virus in relation to volatile compounds - Deswina, Puspita; Kirana, Rinda; Mulya, Karden; Gunaeni, Neni; Sobir; Satyawan, Dani; Nugroho, Kristianto; Terryana, Rerenstradika Tizar; Manohara, Dyah; Musaddad, Darkam; Saadah, Imas Rita; Moekasan, Tonny Koestoni (Penerbit Universiti Kebangsaan Malaysia, 2025)
The Pepper Yellow Leaf Curl Indonesian (PYLCI) virus, transmitted by the whitefly, has a significantly detrimental impacts on the productivity of hot peppers. Despite the implementation of extensive breeding programs, the development of varieties resistant to PYLCI remains a challenging endeavor. This study proposes a novel strategy that considers vector-host interactions with the objective of enhancing resistance. A total of 37 genotypes of hot pepper, collected by IPB University and the National Research and Innovation Agency (NRIA), along with two registered varieties of hot pepper (Bonita and Sigantung), were utilized in this study. The results were classified into five categories based on the disease reaction observed in the tested genotypes. The IPB RF 41 genotype exhibited high resistance, with no instances of diseases and minimal symptom intensity. In contrast, the IPB RF 20 genotype demonstrated high susceptibility, with a 64% incidence of disease and a symptom intensity of 41.85%. The distribution of the whitefly was consistent across the area, with an average of 29–39 imagos per week in each trap. The flowers and leaves of the CR-2022-46 (resistant) and IPB RF 29 (susceptible) genotypes were found to contain volatile compounds. The resistant genotypes exhibited a reduced number of volatile floral compounds. Leaf analysis showed the presence of D-limonene, indole, naphthalene, 1.4.5-trimethyl-, whereas these compounds were not detected in the flowers. Conversely, α-fenchene and naphthalene, 2-methyl-, were found exclusively in the flowers. Beta-ocimene plays a role in the whitefly-hot pepper interaction, with varying patterns of increasing from the vegetative to generative phases between resistant and susceptible genotypes. Resistant plants released higher levels of (E)-4,8-Dimethylnona-1,3,7-triene (DMNT) in both phases. This information could prove beneficial for the further development of alternative breeding programs focused on PYLCI resistance, and potentially revolutionize the agricultural practices in Indonesia.